APPLICATION OF BESSEL’S DIFFERENTIAL EQUATION SOLUTIONS J (x) p IN FOOD ENGINEERING - Marín-Machuca, Olegario (2020)
The Bessel expression is an ordinary diff erential equation of second order (EDOPO), whose solutions are spherical and can be solved by Frobenius' methods, indeterminate series, and coeffi cients; whose values can be used very well and easily in food engineering and technology. Their solutions are specifi ed in four parts, of which those of the type are those that have an application in the present study. The Bessel EDOPO was solved in its four possibilities, in which the values and behaviors are given in tables and graphs in detail. Th e corresponding values were used in the temperature distribution for cylindrical containers of known dimensions using the equations of heat transfer by conduction, preferably, coming from the Fourier theory, facilitating the improvement, modifi cation, and design of new processes. The results of the temperature distribution were calculated by the respective equations and the results obtained were satisfactorily used in the development of the work.